2019
DOI: 10.1590/1807-3107bor-2019.vol33.0038
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of universal adhesive system to enamel surrounding real-life carious cavities

Abstract: This study aimed to evaluate the bond strength of a universal adhesive system to enamel surrounding real-life carious cavities. Twentyeight permanent molars (n = 7) with carious lesions in dentin were subjected to selective carious tissue removal to firm dentin and had their crowns sectioned longitudinally. A universal adhesive system (Single Bond Universal [SBU] used in either etch-and-rinse and self-etch strategies) was compared with an etch-and-rinse Adper Single Bond 2 (ASB) and a selfetch Clearfil SE Bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
7
1
4
Order By: Relevance
“…1). The bonding to enamel should be a concern, since the stability of the resin-bonded dentin (18) and effectiveness of marginal sealing (19) depends on the bonding to surrounding enamel (20). Adherence results in the current study did not show statistically significant difference between the UE and ET groups.…”
Section: Discussioncontrasting
confidence: 54%
“…1). The bonding to enamel should be a concern, since the stability of the resin-bonded dentin (18) and effectiveness of marginal sealing (19) depends on the bonding to surrounding enamel (20). Adherence results in the current study did not show statistically significant difference between the UE and ET groups.…”
Section: Discussioncontrasting
confidence: 54%
“…The initial literature review identified records of 2,880 duplicates. In addition to 1,177 studies reviewed in the title and abstract, 45 studies were left to be read in full, 31 of them were not included, among them, 13 articles evaluate dentin micro-shear bond strength which was different from dentin micro-tensile bonding strength [38][39][40][41][42][43][44][45][46][47][48][49][50] .…”
Section: Search Strategymentioning
confidence: 99%
“…As far as bonding strength, the most reliable bonding occurs in restorations where the margin is in enamel. 1 If the DGM is completely in enamel, the lesion should be removed ( Fig. 2 -(Ai,①)), but if DGM is close to CEJ ( Fig.…”
Section: Decision Treementioning
confidence: 99%
“…However, they are also one of the most common categories to experience failures, mainly due to weaker adhesion caused by dental enamel at the gingival margin. 1 One possible way to alleviate this problem is to address caries detection tools and apply them to treat the disease. Several studies have reported different approaches to detect carious tissue, such as red fluorescence, infrared transillumination, detecting dies, chemo-mechanical caries removal, self-limiting polymer burs, fluorescence cameras, optical coherence tomography, and lasers.…”
Section: Introductionmentioning
confidence: 99%